Studies on methotrexate cytotoxicity and apoptosis in human B-lymphocyte cell lines : with emphasis on 5,10-methylenetetrahydrofolate reductase 677C→T genotype and folate status - Gallagher, Muriel (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2011)
Methotrexate (Mtx) is an antifolate drug which is widely used in treatment of cancer and of autoimmune and inflammatory conditions. The main mechanism by which Mtx operates is inhibition of dihydrofolate reductase (DHFR), thereby preventing the regeneration of the active folate cofactor THF, leading to a blockade of intracellular folate metabolism. Folates are required for many cellular reactions, most notably synthesis of DNA precursor molecules and for generation of the universal methyl-group donor, S-adenosylmethionine (SAM). Mtx therefore interferes with a metabolic pathway which is linked to many diverse cellular processes. Despite appreciation of the drug's clinical efficacy, the precise mechanism by which Mtx has its effects within the cell is incompletely understood. A key area of interest is the potential influence of pharmacogenomic factors on individual responses to Mtx. There is a common 677C →T polymorphism in MTHFR, an enzyme which occupies a key regulatory point in the folate metabolic pathway. The minor allele of this polymorphism is associated with reduced MTHFR activity, increased plasma homocysteine (Hcy) and altered distribution of folate cofactors within the cell. Several clinical association studies have suggested that the MTHFR 677C→T polymorphism may affect Mtx efficacy or toxicity, but there is a lack of biochemical evidence to test these reports.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin